Purslane Herb (Portulaca grandiflora) Ointment Antibacterial Potency against Staphylococcus aureus - Purwanto, Agus; Budiawan, Antonius; Nugroho, Christianto Adhy; Indriasari, Christina (UNIVERSITAS PGRI MADIUN, 2024)
Recent research showed that the rose-like purslane (Portulaca grandiflora) magenta flower variety herbs ethanolic extract has antimicrobial potency. This research aims to determine the purslane herbs (Portulaca grandiflora) extract ointment antimicrobial potency against Staphylococcus aureus. Ointment base formulation contained of vaseline album, cera alba, adeps lanae, paraffin liquidum, cetyl alcohol, nipagin, and nipasol. Extract ointment was prepared by mixing the extract with 10, 20, and 30% concentrations into the ointment base. The antimicrobial activity test conducted in vitro using the paperdisk difussion method. The antimicrobial activity test result of the three extract concentrations of ointments showed that the 30% extract ointment had antimicrobial effect on Staphylococcus aureus with 0.81±0.03cm of clear zone. The antimicrobial activity test demonstrated that 30% purslane herbs (Portulaca grandiflora) extract ointment has a potency as antimicrobial against Staphylococcus aureus.